PENDAMPINGAN KULIAH KERJA NYATA MAHASISWA PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM), DALAM ASPEK ENTREPRENEURSHIP, DAN DIGITALISASI BISNIS. - Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Moch Irwan Hermanto, Moch Irwan Hermanto; Abdussalam, Abdussalam; Jiehad Akbar Pria Utama, Jiehad Akbar Pria Utama; Musyfiq Amrullah , Musyfiq Amrullah; Asep Wasid , Asep Wasid (Media Nusantara, 2024)
The background to the initiative for assistance to implement KKN in Cinanggerang Village is to overcome the economic challenges faced by the village community, increase understanding and skills related to MSMEs, entrepreneurship, and develop business digitalization, so that Cinanggerang Village can develop better economically and create opportunities. better for local communities to improve and enhance their quality of life. Objectives of KKN The objectives of implementing this KKN are: 1. Increasing the understanding and skills of the Cinanggerang Village community in the fields of MSMEs, Entrepreneurship and Business Digitalization. 2. Help promote local products, such as palm sugar, through creating a sales website. 3. Provide a positive contribution and real role to the community and develop a sense of love for local businesses around Cinanggerang Village. Benefits of KKN It is hoped that the implementation of this KKN will provide the following benefits: 1. The people of Cinanggerang Village can improve their understanding and skills in developing MSME businesses and digitalizing business. 2. Increase sales of local products, especially palm sugar, through the sales website created. 3. Improving the quality of life of the people of Cinanggerang Village through local business development. 4. Nusantara Islamic University students can truly dedicate themselves to society and develop their social competence.